2008
DOI: 10.1001/archsurg.143.11.1062
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Long-term Outcome of Young Patients With Gastric Carcinoma According to Sex

Abstract: Background: We investigated the clinicopathological features and evaluated the prognostic impact of age and sex on patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 27 publications
(43 reference statements)
3
27
2
5
Order By: Relevance
“…OR odds ratio; CI confidence interval * The multivariate logistic regression test was used age affects lymph node metastasis in poorly differentiated EGC and signet ring cell EGC [18][19][20]. However, our study shows that if a patient with poorly differentiated EGC was younger than 45 years, the risk of lymph node metastasis was 2.6 times higher than that in a patient older than 45 years.…”
Section: \00001mentioning
confidence: 60%
“…OR odds ratio; CI confidence interval * The multivariate logistic regression test was used age affects lymph node metastasis in poorly differentiated EGC and signet ring cell EGC [18][19][20]. However, our study shows that if a patient with poorly differentiated EGC was younger than 45 years, the risk of lymph node metastasis was 2.6 times higher than that in a patient older than 45 years.…”
Section: \00001mentioning
confidence: 60%
“…However, some authors indicate that the reason lies in co-morbidities and deaths not related to cancer. On the other hand, there are reports that suggest poorer prognosis in younger patients in whom undifferentiated forms of gastric cancer are more common [24].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [15] reported that young women with gastric cancer showed unfavorable prognoses, and Sato et al [16] reported that survival after surgery for gastric cancer was slightly more favorable in women. Wichmann et al [17] reported that women with colorectal cancer had more favorable outcomes than men.…”
Section: Discussionmentioning
confidence: 99%